A Legal Analysis of the Responsibility of the Transportation Department of Sukoharjo Regency in Ensuring the Health and Safety of Road Users - Narendra Bintang Khatulistiwa; Aris Prio Agus Santoso; Muhamad Habib (The Easta Journal Law and Human Rights, 2026)
This study aims to analyze juridically the responsibility of the Transportation Agency of Sukoharjo Regency in ensuring the health and safety of road users. The research focuses on two main issues: the legal framework governing the agency’s responsibility and the implementation of such responsibility in the administration of traffic and road transportation.This research employs a normative legal method using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary sources, which are analyzed qualitatively. The primary legal basis of this study refers to Law Number 22 of 2009 concerning Road Traffic and Transportation. The results indicate that, from a juridical perspective, the Transportation Agency of Sukoharjo Regency holds administrative and technical responsibilities in traffic management, including regulation, supervision, control, and the provision of infrastructure that meets safety and health standards. These responsibilities reflect the principles of legality and good governance. However, in practice, several obstacles remain, such as limited budget, inadequate infrastructure, and suboptimal inter-agency coordination. Therefore, strengthening regulations, enhancing supervision, and optimizing the role of local government are necessary to ensure the fulfillment of the public’s right to health and safety in road usage.